El linchamiento del obispo Jorge y la violencia religiosa tardorromana - Aja Sánchez, José Ramón (Antigüedad y Cristianismo, 1991)
This article describes the events which took place during the fourth century in Alexandria when the bishop George and his two civil servants were murdered by a rioting mob. The unpopular activities of the bishop towards the orthodox Christians and the pagans are considered the principal cause of the outbreak of the disturbances. The rehgious controversies of the fourth century, the internal conflicts amongst the Christians and the popular rebellions in the background for the events which took place. The influence of these conflicts on the population and on the cities are considered as the productos of a new reality: the presence of Christianity as a religio licita in the religious and civil scene during the Lower Empire.